A Model of Empowering Children in Orphanages Through Zero-Waste Textile Craft: A Study in an Gunungan Surakarta Orphanage - Nadia Sigi Prameswari; Dwi Candra Purnamasari; Ratih Ayu Pratiwinindya; Maria Krisnawati; Moh. Yudik Al-Faruq (Universitas Ibn Khaldun, 2026)
This community service offers a strategic solution in the form of strengthening the creative capacity of zero-waste textile craft based on upcycling industrial waste fabric scraps through collaboration with the Gunungan Surakarta Orphanage located in the industrial center area of Kampung Blangkon Potrojayan which is famous for its blangkon crafts. Kampung Blangkon Surakarta is known as a blangkon craft center that accommodates 40 active craftsmen with unique designs as a local cultural identity. However, the production process produces 25 kg of scrap fabric waste per week that has not been systematically managed and the waste is always thrown away without added value. On the other hand, craftsmen still focus on the main product blangkon without developing derivative designs based on waste, so the potential for product diversification and strengthening the creative economy based on sustainability has not been optimal. Textile waste is identified and processed into valuable craft products such as souvenirs and unique accessories through the sustainable Participatory Action Research (PAR) method, including training in knowledge of patchwork materials, craft design techniques with upcycling methods, product management and marketing strategies, as well as attractive and valuable packaging techniques. This program aims to strengthen the creativity of orphanage children by optimizing production waste management and developing a sustainable social enterprise model. The urgency of collaboration lies in creating synergy between the creative industry and social institutions in building a community-based circular economy ecosystem. With this integrated approach, this innovation is expected to increase the added value of textiles while simultaneously promoting the sustainable economic independence of orphanage groups.